India : Financial Sector Assessment Program-Detailed Assessments Report on CPSS IOSCO Recommendations for Securities Settlement Systems and Central Counterparties. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses findings of the assessments on Committee on Payment and Settlement Systems-International Organization of Securities Commissions (CPSS-IOSCO) Recommendations for Securities Settlement Systems and Central Counterparties in India. The results indicate that, in general, the risk management framework for the securities and derivatives clearing and settlement systems in India is prudent. The operational reliability is high, and the regulation and oversight functions are effective. The National Payments System in India has undergone a major reform, in particular the securities and derivatives clearing and settlement systems. These systems are comprehensive and designed to minimize risks in the rapidly developing securities and derivatives markets.